Answer:
![\large\boxed{x^2+y^2+4x-2y+1=0}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/yv3a2ofzexpwiguvutf8ezq4cnwucdqti1.png)
Explanation:
The standard form of an equation of a circle:
![(x-h)^2+(y-k)^2=r^2](https://img.qammunity.org/2020/formulas/mathematics/high-school/kmmm139x85fjht54s8zz0668styzp2e6cm.png)
(h, k) - center
r - radius
The general form of an equation of a circle:
![x^2+y^2+Dx+Ey+F=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7vehu8y5ws2l4z9p7mdkq8f65gzyty3t3m.png)
We have the center (-2, 1). Substitute to the equation in the standard form:
![(x-(-2))^2+(y-1)^2=r^2\\\\(x+2)^2+(y-1)^2=r^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/c71qj778d8p3zyn98aimwssb0kwzomwtn1.png)
Put thr coordinates of the point (-4, 1) to the equation and calculate a radius:
![(-4+2)^2+(1-1)^2=r^2\\\\r^2=(-2)^2+0^2\\\\r^2=4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/bwzf5q18jytpq2ece8icnkp0nyfcihbcec.png)
Therefore we have the equation:
![(x+2)^2+(y-1)^2=4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jnof5smcw2xzpr8ho57y2n34bdn3barw98.png)
Convert to the general form.
Use
![(a\pm b)^2=a^2\pm 2ab+b^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/c9chdhk5vfsam5hyf6bmg0j49djrqjrx9z.png)
![(x+2)^2+(y-1)^2=4\\\\x^2+2(x)(2)+2^2+y^2-2(y)(1)+1^2=4\\\\x^2+4x+4+y^2-2y+1=4\qquad\text{subtract 4 from both sides}\\\\x^2+y^2+4x-2y+1=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/p2gbd5960f4up72p4beyjy8kufgdh71gti.png)